Chemical diplomacy in male tilapia: urinary signal increases sex hormone and decreases aggression - Saraiva, João (2018)
Androgens, namely 11-ketotestosterone (11KT), have a central role in male fish reproductive physiology and are thought to be involved in both aggression and social signalling. Aggressive encounters occur frequently in social species, and fights may cause energy depletion, injury and loss of social status. Signalling for social dominance and fighting ability in an agonistic context can minimize these costs. Here, we test the hypothesis of a 'chemical diplomacy' mechanism through urinary signals that avoids aggression and evokes an androgen response in receiver males of Mozambique tilapia (Oreochromis mossambicus). We show a decoupling between aggression and the androgen response; males fighting their mirror image experience an unresolved interaction and a severe drop in urinary 11KT. However, if concurrently exposed to dominant male urine, aggression drops but urinary 11KT levels remain high. Furthermore, 11KT increases in males exposed to dominant male urine in the absence of a visual stimulus. The use of a urinary signal to lower aggression may be an adaptive mechanism to resolve disputes and avoid the costs of fighting. As dominance is linked to nest building and mating with females, the 11KT response of subordinate males suggests chemical eavesdropping, possibly in preparation for parasitic fertilizations.